2020
DOI: 10.1007/s13300-020-00894-y
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Semaglutide: An Oral Glucagon-Like Peptide 1 Receptor Agonist in Management of Type 2 Diabetes Mellitus

Abstract: Glucagon-like peptide 1 receptor agonists (GLP-1 RAs) are a well-established class of glucose-lowering drugs. GLP-1 RAs can be classified according to their structure, duration of action and mode of administration. This review describes the basic and clinical pharmacology of orally administered semaglutide. It highlights the PIONEER clinical trial programme results, and reviews the efficacy, safety and tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…Semaglutide is available in oral formulations due to the presence of sodium N‐(8‐[2‐hydroxybenzoyl] amino) caprylate, which inhibits its degradation 62 . Semaglutide reduces the risk of diabetic kidney disease but increases the risk of retinopathy 63 .…”
Section: Resultsmentioning
confidence: 99%
“…Semaglutide is available in oral formulations due to the presence of sodium N‐(8‐[2‐hydroxybenzoyl] amino) caprylate, which inhibits its degradation 62 . Semaglutide reduces the risk of diabetic kidney disease but increases the risk of retinopathy 63 .…”
Section: Resultsmentioning
confidence: 99%
“…Applicability of the GLP-1 receptor agonist as a pill will allow for a simple initiation, maintenance and/or intensification of therapy, easing the fear of patients for injection therapy. Therefore, better adherence and less therapeutic inertia is expected with the use of oral semaglutide [35,37]. Based on the authors' clinical practice experiences, we have observed that individuals generally do not fully understand the difference between non-insulin and insulin injections.…”
Section: Discussionmentioning
confidence: 99%
“…Semaglutide is a GLP-1 RA that can be used subcutaneously once a week as a treatment for T2D [ 30 , 31 ]. This injectable molecule is a potent and long-acting GLP-1 analog with 94% homology with human native GLP-1 [ 32 ]. Three key structural differences provide the extended pharmacokinetics of this drug, namely, the substitution of Ala with Aib at position 8 that increases enzymatic (DPP4) stability, attachment of a linker and C18 di-acid chain at position 26 that provides strong binding to albumin and substitution of Lys with Arg at position 34 that prevents C18 fatty acid-binding at the wrong site [ 32 ].…”
Section: Development Of Oral Semaglutide: a Glp-1 Ra Peptidementioning
confidence: 99%
“…This injectable molecule is a potent and long-acting GLP-1 analog with 94% homology with human native GLP-1 [ 32 ]. Three key structural differences provide the extended pharmacokinetics of this drug, namely, the substitution of Ala with Aib at position 8 that increases enzymatic (DPP4) stability, attachment of a linker and C18 di-acid chain at position 26 that provides strong binding to albumin and substitution of Lys with Arg at position 34 that prevents C18 fatty acid-binding at the wrong site [ 32 ]. The phase 3 clinical trial program (SUSTAIN) compared subcutaneous semaglutide to placebo or other active standard-of-care medications in patients with T2D [ 30 , 31 ].…”
Section: Development Of Oral Semaglutide: a Glp-1 Ra Peptidementioning
confidence: 99%